2020
DOI: 10.1037/pspp0000223
|View full text |Cite
|
Sign up to set email alerts
|

The role of sensation seeking in political violence: An extension of the Significance Quest Theory.

Abstract: Adventure and excitement have often been invoked to explain why people engage in political violence, yet empirical evidence on the topic has thus far been anecdotal. The present research sought to fill this gap in knowledge by examining the role of sensation seeking in political violence and integrating this concept with Significance Quest Theory (Kruglanski, Chen, Dechesne, Fishman, & Orehek, 2009; Kruglanski et al., 2013). Extending prior research on violent extremism, Study 1 found that sensation seeking me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 118 publications
2
71
1
3
Order By: Relevance
“…Additionally, we tested the role of significance loss experienced by activists in relation to the cause. In contrast to past research that demonstrated effects of frustrated significance need on collective action (Dugas et al., ; Schumpe, Bélanger, Moyano, & Nisa, ), in most of our studies significance loss did not significantly predict activist intentions. Moreover, when we statistically compared the strength of the effects of significance loss and significance gain it turned out that in majority of cases the effect of significance gain on willingness to sacrifice and/or activist intentions was stronger than the effect of significance loss .…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we tested the role of significance loss experienced by activists in relation to the cause. In contrast to past research that demonstrated effects of frustrated significance need on collective action (Dugas et al., ; Schumpe, Bélanger, Moyano, & Nisa, ), in most of our studies significance loss did not significantly predict activist intentions. Moreover, when we statistically compared the strength of the effects of significance loss and significance gain it turned out that in majority of cases the effect of significance gain on willingness to sacrifice and/or activist intentions was stronger than the effect of significance loss .…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, their small size is typical of what can be found in the Significance Quest literature (e.g. Webber et al, 2017;Schumpe, Bélanger, Moyano, & Nisa, 2018). We were able to replicate the mediation models from Study 1 with the exception that, in this study, indirect effects of the LoS manipulation were not found for intentions to engage in Armed Struggle but were significant as regards Activism.…”
Section: Discussionsupporting
confidence: 73%
“…Also, individuals who have experienced significant economic or relational loss are more likely to engage in violent actions (Jasko, LaFree, & Kruglanski, 2016). There is now ample evidence for a causal role of Loss of Significance (LoS) in generating violent political behavior (Jasko, Lafree, & Kruglanski, 2016;Webber et al 2017;Schumpe, Bélanger, Moyano, & Nisa, 2018).…”
Section: Political Violence and Significance Motivesmentioning
confidence: 99%
“…Although the construct of passion has been originally discussed as a stable individual difference (Vallerand et al, ), mounting evidence also indicates that harmonious and obsessive passion can be experimentally induced (see Bélanger et al, ; Lafrenière, Vallerand, & Sedikides, ; Schellenberg, Bailis, & Mosewich, ). Many psychological constructs have been shown to behave in the same way (e.g., locomotion and assessment, sensation‐seeking; see Higgins, Pierro, & Kruglanski, ; Orehek, Mauro, Kruglanski, & van der Bles, ; Schumpe, Bélanger, Moyano, & Nisa, ), thus substantiating Higgins’ propositition that the concept of personality is “one source of variability in the functioning of psychological principles that also varies across momentary situations” (, p. 612). This suggests that passion is dynamic and can be alternatively operationalized as an individual difference or as an expression of situational forces (e.g., Kruglanski & Sheveland, ; Sturaro, Denissen, van Aken, & Asendorpf, ).…”
Section: The Dualistic Model Of Passionmentioning
confidence: 82%